PENEGASAN DAN PENGUATAN MAKNA PADA HEADLINE BERITA TVONENEWS - Sari, Suci Rahmah; Ernawati, Yeni (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2023)
Abstract This research aims to describe the use of dysphemia and euphemism in tvOneNews headlines. The theory used as a reference by the researcher is Chaer's theory (2013). Chaer's theory states that there are causative factors that affect meaning change, namely there are 5 types of meaning change including widening, narrowing, euphemia, dysphemia, and total change. The research method used is qualitative with a case study approach. The data source taken is in the form of news headlines on tvOneNews Investigation and Crime: "Telusur". The data collection technique is listening and noting. The data analysis technique was carried out in several stages, namely classifying the data, analysing the data, and concluding the results. The results of the research found the use of diphthaemia as much as 18 data and euphthaemia 17 data, and the changes occurred in words and phrases. Interpreting from this research, the use of dysphemia in news headlines on tvOneNews is more than euphemia. The use of more dysphemia can refer to Chaer's theory that this use can give an effect of assertiveness, and reinforcement of meaning in a sentence, tvOneNews uses it in its news headlines displayed on the YouTube platform to be able to give that effect.